Estudo de caso da configuração dos elementos da interface presente no jogo Dead Space - Queiroz, Brenda Lee de Paula Rocha (2023)
The video game market has experienced an increase in the number of consumers in recent years and as a result thousands of games are launched annually to meet this demand. With so many options available on online platforms and retail stores, one way to get the average player's attention is through the game's presentation, which ranges from choosing a certain art aesthetic to the application of new mechanics made possible by different types of interfaces. Present results indicate that the UI of the observed game mostly uses diegetic and overlapping elements, favoring the clarity of the transmitted information, the inclusion of the minimum of actions necessary to achieve a complete interaction and the simplification of the elements when there is no need for complexity.